Evaluation of Forest Honey on the Proliferation and Migration of Dermal Fibroblasts under Hyperglycemic Conditions: An In Vitro Study - Januar Rizqi; Denny Agustiningsih; Dwi Aris Agung Nugrahaningsih (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aims to evaluate the effect of forest honey on fibroblast proliferation and migration under hyperglycemic conditions in vitro. The research method involved culturing primary fibroblasts in high-glucose DMEM (25 mM) and dividing them into five groups: standard control (standard medium), hyperglycemia control (high-glucose medium without treatment), 3% honey, 1.5% honey, and 0.75% honey. Proliferation was assessed by counting live cells (Trypan Blue staining/hemocytometer) at 24, 48, and 72 hours. Migration was measured using a scratch assay (0, 24, 48, 72 hours) and analyzed with ImageJ. The Shapiro–Wilk test was used for normality; data were analyzed with ANOVA followed by LSD or Kruskal–Wallis (p<0.05). Results showed that hyperglycemia decreased proliferation compared to the standard control. Treatment with 1.5% honey and 0.75% honey consistently increased proliferation compared to the hyperglycemic control at all time points (p<0.05), while 3% honey showed a relatively lower increase. The standard control group achieved 100% closure at 72 hours in the migration variable. The honey groups (0.75–3%) showed an increase compared to the hyperglycemic control, but the difference was not significant at 24–48 hours and approached significance at 72 hours (p=0.057). In conclusion, forest honey at a concentration of 1.5% can increase fibroblast proliferation in a hyperglycemic environment. The effect on migration requires confirmation with osmolality controls and more sensitive endpoints. These findings provide a biological basis for developing honey-based diabetic wound care adjuvants focusing on dose optimization and formulation standardization.